The Value of Humanistic Education in the Novel of Orang-Orang Biasa Andrea Hirata's Works And Its Relevance in Literature Learning at Senior High School Number 1 Muaradua - Herlina; Fitriani, Yessi; Ardiansyah, Arif (Jurnal Pendidikan Tambusai, 2021)
This research has the following objectives: (1) to describe the form of humanistic education contained in the novel Orang-Orang Biasa by Andrea Hirata (2) to know and describe the relevance of humanistic education in the novel Orang-Orang Biasa in Indonesian literature learning at SMA Negeri 1 Muaradua. The data analysis technique used is the content analysis technique. Data collection techniques in this study by means of direct observation and external documentation. The results of the research prove that the value of humanistic education in the novel Orang-Orang Biasa consists of material values, vitality, spirituality, respect for other people's opinions, cooperation, willingness to sacrifice, caring for others, helping to help, and solidarity. The novel Orang-Orang Biasa by Andrea Hirata can be implemented in class XI SMA Negeri 1 Muaradua.